Educational Management in Brazil as a Factor Impacting the Quality of Public Schools - Moura Mandolini, Ana Claudia; Lopes Reis, Márcia (Emerging Trends in Education, 2025)
The document analyzes the systematization of literature in Brazil under the impact of educational management and the quality of Brazilian public schools. The criteria for large-scale tests and exams are recognized as evaluations that define what constitutes quality education. In this context, the role of management appears to represent a significant impact factor. The chosen methodology was qualitative, using content analysis. The stages included the selection of articles from databases and eligibility criteria delimiting the period between 2014 and 2024. Based on eligibility criteria such as keywords and material type in the Scielo and Oasis.br databases and in the UNEPS, USP, and UNICAMP repositories, 19 articles were listed for discussion. The analyses were conducted using codes/categories: function, profile, and management practices. The conclusions allow for the systematization of changes in management — typically democratic — towards the "platform" of its daily activities to achieve results in large-scale evaluations that indicate which schools provide quality public education.